THE APPLICATION OF SOFTWARE BASED TECHNOLOGY FOR PROJECT IDENTIFICATION – A CASE STUDY OF SPACE SYNTAX ANALYSIS - Mathivathany, S.; Nanthagopan, Y.; Thirugnanasampanthar, S.; Rukshan, A. (University of Jaffna, 2019)
Project identification is to develop a preliminary proposal for the most appropriate set of interventions and course of action, within a specific time and budget frames, to address a specific development goal in a particular region or setting. Project success is decided on best project identification, which guides in setting project objectives to solve a given development problem or to use the opportunity for the development of a particular aspect. The "Space Syntax Analysis" is a science-based Geographical Information System (GIS). In practice, the space syntax provides a major project planning information including patterns of movement, density, land use and land value, urban growth and societal differentiation which can be used for generation and evaluation of project ideas. The research objective is to identify the usage of space syntax technology in project identification. Moratuwa, which is a large suburb of Colombo city, was selected to investigate the relationships between spatial layout and project identification. The criteria were used for connectivity levels using space syntax analysis methods such as very high, high, moderate, low, and very low. New development project ideas were generated using the space syntax analysis. The result of this study helps to identify the new projects ideas and valuable information for stimulating innovation of regions for sustainable development.
Keywords: Geographical information system; project identification; project success; space syntax analysis; sustainable development